Philippine medical thesaurus on anatomy digestive system, embryonic structures and urogenital system in Iluko - Manzano, Mel Joseph D.; Tarlit, Rodolfo Y. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2014)
This study sought to come up with a medical thesaurus on terms relevant to the digestive system, embryonic structures, and urogenital system of the human body utilizing words from the Iluko language; their relationship among each other and the correct pronunciation of the translated terms.
The top-down approach in thesaurus construction was used in this study. The top-down approach collects terms from previously constructed indexing languages and from subject specialists who will provide words that they think are appropriate. All first language speakers of Iluko in the province of Zambales, specifically in the municipalities of San Antonio and San Marcelino were the population of the study. Two medical doctors, one dentist, and two health center staff of the said province were chosen as respondents for the study. The researcher utilized the recent making of dictionaries that were used by the previous group who translated MeSH and were able to come up with their medical thesaurus (Sirios and Simbulan, 2003).
Triangulation was done wherein the data were checked and counter-checked in the other sources to verify the correct usage, synonymy, and other properties of a given term. Due to the large in information at hand, the researcher followed the guidelines of the previous studies with the same topic in different languages (Hizon and Roque, 2003), and with different topics of the same languages (Simbulan and Sirios, 2004). However, the researcher devised an additional guideline as regards discrepancies of terms between the respondents and dictionaries.
Out of 226 MeSH terms, the researcher came up with only 119 translated terms. The low output of translation in Iluko indicates the difficulty in translating MeSH terms from the said subcategories. The study somehow verifies the complexities on degrees of equivalence listed in ISO 5964.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Subject headings, Ilocano -- Medicine; Subject headings, Ilocano -- Digestive system; Subject headings, Ilocano -- Embryology, Human; Subject headings, Ilocano -- Genitourinary organs; Ilocano language -- Medical Ilocano